2016
DOI: 10.1039/c6fo00743k
|View full text |Cite
|
Sign up to set email alerts
|

Blackberry, raspberry and black raspberry polyphenol extracts attenuate angiotensin II-induced senescence in vascular smooth muscle cells

Abstract: Activation of angiotensin II (Ang II) signaling during aging increases reactive oxygen species (ROS) leading to vascular senescence, a process linked to the onset and progression of cardiovascular diseases (CVD). Consumption of fruits and vegetables, particularly berries, is associated with decreased incidence of CVD, which has mainly been attributed to the polyphenol content of these foods. Thus, the objective of this study was to investigate the role of blackberry (BL), raspberry (RB), and black raspberry (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 57 publications
4
43
0
Order By: Relevance
“…Recently, Ang II was reported to trigger aging of vascular smooth muscle cells (VSMCs) by ARTICLE causing oxidative DNA damage which is intimately linked to the stability of atherosclerotic plaques (Herbert et al, 2008;Matthews et al, 2006). These findings are consistent with the reports that blockade of Ang II activity by polyphenols, such as resveratrol and those found in berries, inhibits vascular senescence-mediated intracellular signaling, leading to blockade of vascular age-associated diseases including atherosclerosis (Feresin et al, 2016;Kim et al, 2018;Najjar et al, 2005). Thus, aging-related vascular disorders may be prevented by controlling cellular senescence.…”
Section: Introductionsupporting
confidence: 72%
“…Recently, Ang II was reported to trigger aging of vascular smooth muscle cells (VSMCs) by ARTICLE causing oxidative DNA damage which is intimately linked to the stability of atherosclerotic plaques (Herbert et al, 2008;Matthews et al, 2006). These findings are consistent with the reports that blockade of Ang II activity by polyphenols, such as resveratrol and those found in berries, inhibits vascular senescence-mediated intracellular signaling, leading to blockade of vascular age-associated diseases including atherosclerosis (Feresin et al, 2016;Kim et al, 2018;Najjar et al, 2005). Thus, aging-related vascular disorders may be prevented by controlling cellular senescence.…”
Section: Introductionsupporting
confidence: 72%
“…The kinases p38MAPK, Akt, and extracellular signal-regulated kinase (ERK)1/2 mediate Ang II-induced effects in VSMCs [ 44 , 45 ]. We previously reported that inhibition of any of these kinases reduced senescence induced by Ang II in VSMCs [ 46 ], suggesting that Ang II-induced senescence is complex, and could be mediated by multiple mechanisms. Some of the molecular mechanisms regulating Ang II-induced senescence reported by us and others are summarized in Figure 2 .…”
Section: Angiotensin II In Mitochondrial Function Nox1 Function mentioning
confidence: 99%
“…These molecules have been reported to have beneficial effects to prevent metabolic syndrome at different levels such as cardiovascular disease and type II diabetes; hence, including blackberry on human diet is beneficial for health (Tavares et al, 2013; Feresin et al, 2016; Sarkar et al, 2016). On the other hand, they play a relevant role in plant defense against biotic and abiotic stress (Daayf et al, 2012).…”
Section: Introductionmentioning
confidence: 99%